Review of the discussion "Culturology in Ukraine: unity in diversity?", which took place online on march 30, 2021 - O. Y. Pavlova, (Ukrainian Cultural Studies, 2021)
The discussion became an attempt to generalize and reflect on understanding not only the subject field of cultural studies in general, the list of its current problems, but, first of all, the peculiarities of its formation in Ukraine.